Observations of the Impacts of Millimeter‐ to Centimeter‐Scale Heterogeneities on Relative Permeability and Trapping in Carbonate Rocks. Issue 4 (7th April 2021) - Manoorkar, Sojwal; Jackson, Samuel J.; Krevor, Samuel
Abstract: Carbonate rock reservoirs are dominated by heterogeneity across a large and continuous range of spatial scales. We study the impact of heterogeneities on relative permeability and residual trapping for three carbonate rocks selected for their distinct spatial scales of rock texture. The Indiana limestone comprises millimeter‐scale heterogeneities, the Estaillades limestone consists of half‐centimeter‐scale heterogeneities, and the Edwards dolomite includes decimeter‐scale heterogeneity. Along with routine characterization of rock samples, steady‐state N2 –deionized water drainage relative permeability measurements are made for each rock at two distinct total flow rates, at least 1 order of magnitude apart. The variation in flow potential across the core results in observations of fluid distribution, core‐average relative permeability, and residual trapping obtained for a range of continuum‐scale capillary number 0.02 < N c = Δ P L H Δ P c < 4.2 . The relative permeability curves for all rocks shift to the right of the water saturation axis with increasing flow potential; the nitrogen relative permeability increases while the water relative permeability decreases. However, the magnitude of the shift depends on the spatial scale of heterogeneity. An inspection of 3D saturation distributions in the cores and estimation of the capillary numbers of flow shows that the rock with the largest heterogeneity is capillary flow dominated throughout the range of injection rates tested; observations in the Indiana and Estaillades carbonates traverse capillary to viscous dominated flow regimes, with commensurate flow rate dependence in the relative permeability. In all cases, residual trapping is poorly described by the Land model. Key Points: Steady‐state multiphase flow is observed with 3D X‐ray CT in three carbonate rocks with mm–dm‐scale heterogeneities Significant heterogeneity can result in decreased flow rate dependency in k r due to the dominance of capillarity over varying viscous flow Residual trapping is poorly described by Land model in highly heterogeneous carbonate rocks